O comportamento informacional de jovens secundaristas e a utiliza????o dos produtos e servi??os da biblioteca: como uma juventude busca pela informa????o - Silva, Grazielle Pereira da (2017)
This work represents a descriptive-exploratory research that aimed to identify the behavior of young high school students in the search for information. The theoretical basis of this work contemplates four main axes: the search for information; Information and communication technologies and their influence on the daily lives of young people; Vocational education at a technical level integrated with secondary education; The school library as a subsidy to school practices and student research. The research was carried out with two subjects: students of the Technical Course in Integrated Administration for Secondary Education, offered by the Federal Institute of Bras??lia (IFB) Campus S??o Sebasti??o; Librarians who work in the 10 (ten) libraries of the IFB campuses. The approaches adopted were as follows: qualitative and quantitative. The questionnaire and the semi-structured interview were used as instruments of data collection. The analysis of the data was based on the content analysis, proposed by Bardin having as categories of research: technological profile and informational behavior of the students; Sources of information used for school work; Degree of satisfaction with the library. The results of this research indicate that students absorb very well the new information technologies and take the use of these to different activities of their daily life. It is noticed that the students use the technologies for search and consumption of the information. The investigated librarians also perceive need to develop certain differentiated aptitudes to act in educational environment.